Effect of crack template structure morphology on electromagnetic shielding efficiency and visual performance of metal mesh optical window - Liqing Yang; Yongmao Guan; Fei Gao; Rui Wan; Pengfei Wang (Results in Engineering)
Electromagnetic shielding optical windows are crucial for protecting photoelectric detection and imaging systems. The template used in metal mesh fabrication significantly affects the electromagnetic shielding and visual performance of these windows. This study explores the preparation of crack templates with varying structural parameters by adjusting the precursor solution. Four different acrylic resin colloids were prepared using water, ethylene glycol, glycerol, and N-methylpyrrolidone (NMP), leading to the creation of four mask templates (DP1–DP4).The morphology and structural characteristics of the templates were analyzed using optical and laser confocal microscopy. DP1, made with water, exhibited the highest edge warping (1.5 µm), whereas DP4, using ethylene glycol and glycerol, showed the least warping (0.3 µm). Infrared spectroscopy revealed that hydrogen bonding in the solvents influenced crack formation, resulting in narrower cracks and smaller periods. Copper meshes were deposited using these templates, with DP1- and DP4-mesh showing average transmittances of 80.2 % and 84.5 %, respectively, across 380–800 nm. Electromagnetic shielding efficiency exceeded 15 dB between 1 and 18 GHz, with DP1-mesh reaching 29 dB at 1 GHz. However, DP1-mesh's larger lines reduced light transmittance, likely due to increased edge warping enhancing line connectivity and reducing breakage.